ANALYSIS OF BU HARTIN RESTAURANT COMPETITIVE STRATEGY IN THE DEVELOPMENT OF CULINARY IN WATES KULON PROGO - Atmoko, T. Prasetyo Hadi; Widyaningsih, Heni (Journal of Indonesian Tourism, Hospitality and Recreation, 2020)
ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui kekuatan dan kelemahan, mengetahui peluang dan ancaman, mengetahui bauran pemasaran dan mengetahui strategi bersaing restoran Bu Hartin. Penelitian ini adalah penelitian kualitatif dengan kunci informan adalah pemilik restoran Bu Hartin dengan Teknik Analisis SWOT. Berdasarkan Analisis SWOT, dapat disimpulkan bahwa faktor kekuatan restoran Bu Hartin memiliki skor 2,36 dan faktor kelemahan memiliki skor 0,08. Faktor peluang memiliki skor 2,99 dan faktor ancaman memiliki skor 0,07. Bauran pemasaran restoran Bu Hartin mencakup tujuh elemen, seperti produk, harga, tempat, promosi, peserta, bukti fisik, dan proses. Hasil dari produk Bu Hartin restaurant adalah menu spesial untuk ayam kampung, iga bakar, dan sup iga. Harga makanan di restoran Bu Hartin terjangkau untuk siswa dan bahkan untuk karyawan kantor. Lokasi restoran Bu Hartin sangat strategis, dekat dengan pusat kota. Promosi untuk restoran Bu Hartin dilakukan melalui media sosial. Restoran Bu Hartin memiliki karyawan yang berpengalaman di bidangnya sehingga layanan kepada pelanggan sangat baik. Fasilitas fisik yang dimiliki oleh restoran Bu Hartin yaitu gazebo yang dapat digunakan sebagai tempat istirahat bagi pelanggan. Proses memasak di restoran Bu Hartin menggunakan bumbu spesial dan lezat sehingga cocok untuk semua tingkat pelanggan. Proses memasaknya cukup cepat, sekitar 10 menit sehingga pelanggan tidak menunggu lama. Berdasarkan diagram SWOT, restoran Bu Hartin berada pada strategi SO dengan meningkatkan promosi melalui media sosial dan memperluas cabang. Kata Kunci: Pengembangan Kuliner, Restoran, Strategi Kompetitif ABSTRACTThe purpose of this research is to find out the strengths and weaknesses, know the opportunities and threats, know the marketing mix and to know the competitive strategy of Bu Hartin restaurant. This research is qualitative research with the key of an informant is the owner of Bu Hartin restaurant with SWOT Analysis Technique. Based on SWOT Analysis, it can be concluded that the strength factor of Bu Hartin restaurant has a score of 2.36 and the weaknesses factor has a score of 0.08. The opportunity factor has a score of 2.99 and the threats factor has a score of 0.07. The marketing mix of Bu Hartin restaurant includes seven elements, such as product, price, place, promotion, participants, physical evidence, and process. The result of the product of Bu Hartin restaurant is a special menu for free-range chicken, grilled ribs, and ribs soup. The food prices at Bu Hartin restaurant are affordable for students and even for office employees. Location Bu Hartin restaurant is very strategic, close to the city center. Promotion for Bu Hartin restaurant is conducted through social media. Bu Hartin restaurant has employees who are experienced in their fields so that the services to the customers are very well. Physical facilities owned by Bu Hartin restaurant that is a gazebo that can be used as a resting place for the customers. The cooking process at Bu Hartin restaurant applies special and delicious spices so that it is suitable for all customers? levels. The cooking process is quite fast, approximately 10 minutes so that the customers do not wait for a long period. Based on the SWOT diagram, Bu Hartin restaurant is on the SO strategy by increasing promotion through social media and expanding branches.   Keywords: Competitive Strategy, Culinary Development, Restaurant